Pulmonary and Physical Rehabilitation in Critically Ill Patients - Myung Hun Jang; Myung-Jun Shin; Yong Beom Shin (Acute and Critical Care, 2019)
Some patients admitted to the intensive care unit (ICU) because of an acute illness, complicated surgery, or multiple traumas develop muscle weakness affecting the limbs and respiratory muscles during acute care in the ICU. This condition is referred to as ICU-acquired weakness (ICUAW), and can be evoked by critical illness polyneuropathy (CIP), critical illness myopathy (CIM), or critical illness polyneuromyopathy (CIPNM). ICUAW is diagnosed using the Medical Research Council (MRC) sum score based on bedside manual muscle testing in cooperative patients. The MRC sum score is the sum of the strengths of the 12 regions on both sides of the upper and lower limbs. ICUAW is diagnosed when the MRC score is less than 48 points. However, some patients require electrodiagnostic studies, such as a nerve conduction study, electromyography, and direct muscle stimulation, to differentiate between CIP and CIM. Pulmonary rehabilitation in the ICU can be divided into modalities intended to remove retained airway secretions and exercise therapies intended to improve respiratory function. Physical rehabilitation, including early mobilization, positioning, and limb exercises, attenuates the weakness that occurs during critical care. To perform mobilization in mechanically ventilated patients, pretreatment by removing secretions is necessary. It is also important to increase the strength of respiratory muscles and to perform lung recruitment to improve mobilization in patients who are weaned from the ventilator. For these reasons, pulmonary rehabilitation is important in addition to physical therapy. Early recognition of CIP, CIM, and CIPNM and early rehabilitation in the ICU might improve patients’ functional recovery and outcomes.